2015
DOI: 10.1002/cam4.430
|View full text |Cite
|
Sign up to set email alerts
|

Intensive care admission of cancer patients: a comparative analysis

Abstract: The aim of this study was to obtain insight into which proportion of cancer patients is admitted to an Intensive Care Unit (ICU) and how their survival, demographic, and clinical characteristics relate to cancer patients not admitted to the ICU. Data from patients registered with cancer between 2006 and 2011 in four hospitals in the Netherlands were linked to the Dutch National Intensive Care Evaluation registry. About 36,860 patients with cancer were identified, of whom 2,374 (6.4%) were admitted to the ICU. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(61 citation statements)
references
References 35 publications
3
49
0
9
Order By: Relevance
“…Approximately 5% to 10% of patients with cancer will develop a life‐threatening condition that necessitates ICU admission . In a study conducted in France, admission rates for patients with differing cancer entities varied between 0.7% and 12% .…”
Section: Evolution Of Critical Care For Patients With Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 5% to 10% of patients with cancer will develop a life‐threatening condition that necessitates ICU admission . In a study conducted in France, admission rates for patients with differing cancer entities varied between 0.7% and 12% .…”
Section: Evolution Of Critical Care For Patients With Cancermentioning
confidence: 99%
“…In a study conducted in France, admission rates for patients with differing cancer entities varied between 0.7% and 12% . Patients with certain malignant diseases, such as esophageal cancer or acute leukemia, and those undergoing allogeneic stem cell transplantation have particularly high ICU utilization rates of up to almost 30% . Currently, patients with malignancies account for approximately 13.5% to 21.5% of all ICU admissions .…”
Section: Evolution Of Critical Care For Patients With Cancermentioning
confidence: 99%
“…This study highlights the evolving complexity of oncology patients, with more lines of treatment available to patients and those with metastatic disease surviving longer and maintaining their performance status. A large registry study has suggested as many as one in 16 cancer patients require intensive care during their treatment . Outcomes are comparable with patients with other chronic organ dysfunction .…”
Section: Discussionmentioning
confidence: 99%
“…Ainda concernente às admissões de pacientes em UTI, estudo holandês [8] demonstrou que mesmo por razões clínicas, o suporte intensivo para pacientes com câncer não deve ser considerado dispensável.…”
Section: N T R O D U ç ã Ounclassified
“…O tipo de câncer mostrou-se como fator influenciador da taxa de mortalidade em três estudos [8,11,12] e a idade influenciou em uma pesquisa [12].…”
Section: R E S U T a D O Sunclassified